Biomarkers of systemic disease in dogs and cats - Whittemore, Jacqueline Christine, author; Lappin, Michael Rex, advisor; Fettman, Martin, committee member; Macy, Dennis Warren, committee member; Hackett, Timothy, committee member (Colorado State University. Libraries, 2007)
Microalbuminuria assays were performed and compared with clinical diagnoses recorded within 3 months of urinalyses in dogs without overt proteinuria and in cats. A Western blot immunoassay was developed and validated for detection of antibodies to Crandell Rees Feline Kidney (CRFK) cell proteins in sera. Immunodominant CRFK proteins were identified. Antibody temporal appearance patterns were determined for cats inoculated with CRFK proteins and cats receiving commercially available FVRCP vaccines. The Western blot immunoassay was adapted to detect CRFK antigens in feline and murine tissues. Associations between CRFK antibodies and vaccination were determined. Associations between CRFK antibodies and biochemical abnormalities were determined in 1,477 privately-owned cats. Dogs positive by the quantitative microalbuminuria assay were 2.3 times as likely to have systemic disease as dogs without microalbuminuria and 2.7 times as likely to have neoplasia. Quantitative microalbuminuria assay results were also significantly associated with age, BUN, and hematuria. Dogs with positive semiquantitative microalbuminuria tests were 4.8 times as likely to have systemic disease and 8.1 times as likely to have neoplasia. Semiquantitative microalbuminuria assay results were also significantly associated with age, BUN, and creatinine. Cats with positive quantitative microalbuminuria results were 6.7 times as like to have underlying disease as cats without microalbuminuria. Quantitative microalbuminuria results were also significantly associated with BUN, pyuria, and hematuria. Cats with positive semiquantitative microalbuminuria assay results were 2.4 times as likely to have underlying disease. Positive semiquantitative microalbuminuria results were significantly associated with serum creatinine, age, pyuria, and hematuria. Gender was not significantly associated with results of either microalbuminuria assay. The urine albumin:creatinine ratio had very poor sensitivity for systemic disease in both species. Crandell Rees Feline Kidney cell protein inoculation was associated with autoantibody development measurable by Western blot immunoassay. Cats receiving commercially available FVRCP vaccines according to a standard vaccination schedule developed antibodies measurable using the validated Western blot immunoassay. Antibody development occurred as early as four weeks after vaccination. The number of antibody bands and density of those bands was greater after one year booster inoculation. Antibody bands developed against antigens 47kD, 40kD and 38kD in size. Immunodominant CRFK antigens were identified as a-enolase, annexin A2, and macrophage capping protein. Wide tissue distributions for a-enolase and annexin A2 were found in cats, consistent with the human literature. Our studies also documented a wide tissue distribution for macrophage capping protein. Significant associations were found between anti-CRFK antibody levels and biochemical abnormalities. There was a significant positive correlation between anti-CRFK antibody levels and serum bilirubin levels. There were significant negative associations between anti-CRFK antibody levels and serum creatinine, ALP activity, and glucose.
Keywords: surgery; medicine